Climate tolerances and trait choices shape continental patterns of urban tree biodiversity. Issue 11 (24th August 2016) - Jenerette, G. Darrel; Clarke, Lorraine W.; Avolio, Meghan L.; Pataki, Diane E.; Gillespie, Thomas W.; Pincetl, Stephanie; Nowak, Dave J.; Hutyra, Lucy R.; McHale, Melissa; McFadden, Joseph P.; Alonzo, Michael
Abstract: Aim: We propose and test a climate tolerance and trait choice hypothesis of urban macroecological variation in which strong filtering associated with low winter temperatures restricts urban biodiversity while weak filtering associated with warmer temperatures and irrigation allows dispersal of species from a global source pool, thereby increasing urban biodiversity. Location: Twenty cities across the USA and Canada. Methods: We examined variation in tree community taxonomic diversity, origins and production of an aesthetic ecosystem service trait in a cross‐section of urban field surveys. We correlated urban tree community composition indicators with a key climate restriction, namely mean minimum winter temperature, and evaluated alternative possible drivers: precipitation, summer maximum temperature, population size and the percentage of adults with a college education. Results: Species accumulation curves differed substantially among cities, with observed richness varying from 22 to 122 species. Similarities in tree communities decreased exponentially with increases in climatic differences. Ordination of tree communities showed strong separation among cities with component axes correlated with minimum winter temperature and annual precipitation. Variation among urban tree communities in richness, origins and the provisioning of an aesthetic ecosystem service were all correlated with minimum winter temperature. Main conclusions: The urban climate tolerance and trait choice hypothesis provides a coherent mechanism to explain the large variation among urban tree communities resulting from an interacting environment, species and human decisions. Reconciling the feedbacks between human decision making and biophysical limitations provides a foundation for an urban ecological theory that can better understand and predict the dynamics of other linked biotic communities, associated ecosystem dynamics and resulting services provided to urban residents.